Enhancing competence and leadership in software development teams through management 3.0 principles - Nesterenko, Ivan; Kopp, Andrii Mykhailovych (Scientific Publishing Center "InterConf", 2024)
This article examines the application of Management 3.0 principles to Agile software development teams, focusing on the fundamental elements of People, Functionality, Quality, Tools, Time, Value, and Process. By maintaining a balance among these parameters, teams and stakeholders can achieve project success. The study considers an Agile software development team as a self-improving system, where self-organization and competency enhancement lead to optimal performance. The research aims to explore a system of continuous competency improvement, with upselling as the key performance factor.
Keywords: agile mindset; upselling; project management; competence; SPIN selling